PathwayMatrix: visualizing binary relationships between proteins in biological pathways. Issue 6 (December 2015) - Dang, Tuan; Murray, Paul; Forbes, Angus
Abstract Background Molecular activation pathways are inherently complex, and understanding relations across many biochemical reactions and reaction types is difficult. Visualizing and analyzing a pathway is a challenge due to the network size and the diversity of relations between proteins and molecules. Results In this paper, we introducePathwayMatrix, a visualization tool that presents the binary relations between proteins in the pathway via the use of an interactive adjacency matrix. We provide filtering, lensing, clustering, and brushing and linking capabilities in order to present relevant details about proteins within a pathway. Conclusions We evaluatedPathwayMatrix by conducting a series of in-depth interviews with domain experts who provided positive feedback, leading us to believe that our visualization technique could be helpful for the larger community of researchers utilizing pathway visualizations.PathwayMatrix is freely available athttps://github.com/CreativeCodingLab/PathwayMatrix .